2020
DOI: 10.1039/d0ra02481c
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotrifluoroethylidenes: an efficient and convenient approach to their synthesis

Abstract: A convenient one step synthesis of chlorotrifluoroalkyl olefins starting from aldehydes was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The incorporation of a CF 3 group into organic compounds represents a popular research area since the obtained analogs usually have improved pharmacological properties. In this context, Roopan et al [76] Xinfeng et al [77] reported a facile and simple way to form 1,1-dichloroalkenes using a new dichloroolefinating reagent…”
Section: Methodologies and Other Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of a CF 3 group into organic compounds represents a popular research area since the obtained analogs usually have improved pharmacological properties. In this context, Roopan et al [76] Xinfeng et al [77] reported a facile and simple way to form 1,1-dichloroalkenes using a new dichloroolefinating reagent…”
Section: Methodologies and Other Casesmentioning
confidence: 99%
“…The incorporation of a CF 3 group into organic compounds represents a popular research area since the obtained analogs usually have improved pharmacological properties. In this context, Roopan et al [76] . synthesized a stable reagent, α ‐chloro‐BT‐sulfone 193 that can react with aldehydes under Julia‐Kocienski olefination conditions to give access to numerous trifluoroalkylidene derivatives.…”
Section: Synthesis Of Trisubstituted Alkenes Via Julia‐kocienski Olef...mentioning
confidence: 99%
“…From the synthesis perspective, 3 exhibits the same behavior as the Julia reagent, which is often used to synthesize olefines from aldehydes. As shown in Figure 2, various chlorotrifluoroethylidenes 4 are obtained by reacting 3 with various aldehydes under basic conditions [35] . The chlorotrifluoroethylidene structure of 4 is important in pyrethroid insecticides and has been constructed by reacting aldehydes with 1,1,1‐trichloro‐2,2,2‐trifluoroethane (CFC‐113a), which is a CFC that negatively affects the ozone layer.…”
Section: Radical Species Produced From Freons and Halothanementioning
confidence: 99%
“…As shown in Figure 2, various chlorotrifluoroethylidenes 4 are obtained by reacting 3 with various aldehydes under basic conditions. [35] The chlorotrifluoroethylidene structure of 4 is important in pyrethroid insecticides and has been constructed by reacting aldehydes with 1,1,1-trichloro-2,2,2-trifluoroethane (CFC-113a), which is a CFC that negatively affects the ozone layer. Current environmental regulations are leading to CFC-113a becoming hard to obtain, so the development of an alternative synthetic approach that does not require CFC-113a has been eagerly anticipated.…”
Section: Electrophilic Radical Species Generated From Freons and Halo...mentioning
confidence: 99%